Withasomniferol d, a new anti-adipogenic withanolide from the roots of ashwagandha (Withania somnifera) - Lee, B.S.; Yoo, M.J.; Kang, H.; Lee, S.R.; Kim, S.; Yu, J.S.; Kim, J.-C.; Jang, T.S.; Pang, C.; Kim, K.H. (MDPI, 2021)
Withania somnifera (Solanaceae), well-known as ‘Indian ginseng’ or ‘Ashwagandha’, is a medicinal plant that is used in Ayurvedic practice to promote good health and longevity. As part of an ongoing investigation for bioactive natural products with novel structures, we performed a phytochemical examination of the roots of W. somnifera employed with liquid chromatography？ mass spectrometry (LC/MS)-based analysis. The chemical analysis of the methanol extract of W. somnifera roots using repeated column chromatography and high-performance liquid chromatog-raphy under the guidance of an LC/MS-based analysis resulted in a new withanolide, withasomnif-erol D (1). The structure of the newly isolated compound was elucidated by spectroscopic methods, including one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) and high-resolution (HR) electrospray ionization (ESI) mass spectroscopy, and its absolute configura-tion was established by electronic circular dichroism (ECD) calculations. The anti-adipogenic activities of withasomniferol D (1) were evaluated using 3T3-L1 preadipocytes with Oil Red O staining and quantitative real-time polymerase chain reaction (qPCR). We found that withasomniferol D (1) inhibited adipogenesis and suppressed the enlargement of lipid droplets compared to the control. Additionally, the mRNA expression levels of adipocyte markers Fabp4 and Adipsin decreased no-ticeably following treatment with 25 μM of withasomniferol D (1). Taken together, these findings provide experimental evidence that withasomniferol D (1), isolated from W. somnifera, exhibits anti-adipogenic activity, supporting the potential application of this compound in the treatment of obesity and related metabolic diseases. ？ 2021 by the authors. Li-censee MDPI, Basel, Switzerland.